Perancangan Interior Model Kit Center Di Surabaya - Gunarto, Dicky; nugroho, martino dwi (Intra, 2015)
The world of hobbies has been rapidly growing in big cities in Indonesia, including Surabaya. One of the hobbies currently developing is collecting model kits. Kikunori Shinohara a professor of neuroscience from Japan, stated that building a model kit couldÂ stimulate blood circulation in the brain which increases oneâ€™s intelligence. From some held gatherings, activities involving model kit are usually held in local mall. To address this phenomenon, it is necessary to create a space containing all activities mentioned above and it is expected to provide a one-stop facility for model kit from the need for information and providing any hobby equipments. This space is also expected to make Surabaya an attraction to the world and to enhance human resource potential as well as economic potential.